1997
DOI: 10.3109/10717549709052011
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline Efficacy in vitro: Cytotoxicity of Liposomal/Nonliposomal Daunorubicin and Doxorubicin for Multiple Tumor Cell Types

Abstract: Anthracyclines, including daunorubicin (DnR) and doxorubicin (DoX), have shown clinical chemotherapeutic utility, albeit in association with cumulative dose-associated cardiotoxicities. Despite structural similarity, however, DnR and DoX treatments have been directed toward leukemias and solid tumor types, respectively. Due to a paucity of in vitro data regarding differential use of DnR or DoX, we assessed the cytotoxicity of these compounds against solid and hematological tumor cell types. In addition, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…For example idarubicin, esorubicin and carcinomycin had inferior response rates to doxorubicin and/or epirubicin (Rozencweig et al, 1984;Bonfante et al, 1986;Lopez et al, 1989). However, in vitro studies indicate that daunorubicin has equivalent cytotoxicity to doxorubicin in breast adenocarcinoma lines (Wiles et al, 1997). Furthermore, a preliminary report presented by Hupperets et al (1996) indicated that DaunoXome 100 mg m 2 every 21 days for up to 24 weeks had encouraging single agent anti-tumour activity in metastatic breast cancer with objective tumour responses in three and stable disease in seven out of 11 treated patients (Anonymous, 1996).…”
mentioning
confidence: 99%
“…For example idarubicin, esorubicin and carcinomycin had inferior response rates to doxorubicin and/or epirubicin (Rozencweig et al, 1984;Bonfante et al, 1986;Lopez et al, 1989). However, in vitro studies indicate that daunorubicin has equivalent cytotoxicity to doxorubicin in breast adenocarcinoma lines (Wiles et al, 1997). Furthermore, a preliminary report presented by Hupperets et al (1996) indicated that DaunoXome 100 mg m 2 every 21 days for up to 24 weeks had encouraging single agent anti-tumour activity in metastatic breast cancer with objective tumour responses in three and stable disease in seven out of 11 treated patients (Anonymous, 1996).…”
mentioning
confidence: 99%
“…These ndings may re ect the physical properties of L PEG -DoX, in which a hydrophilic coating of PEG shields the liposome from interactions with soluble molecules and the cell surface (Cabanes et al 1998;Gabizon and Martin 1997;Goren et al 1996;Horowitz, Barenholz, and Gabizon 1992;Papahadjopoulos, Allen, and Gabizon 1991). Reduced in vitro cytotoxic activity of L PEG -DoX, compared with that of DoX, has been reported for a variety of tumor cell lines (Wiles et al 1997) and may be related to reduced release of DoX from the aqueous interior of the liposomes, or it may re ect reduced cellular contact with DoX associated with the liposome bilayer. Bearing in mind evidence that DoX has the capability of inducing cytotoxicity without internalization, the steric barrier effect produced by PEG may hinder DoX/cell interactions, resulting in the inability of L PEG -DoX to initiate early apoptosis.…”
Section: Figurementioning
confidence: 86%
“…3). Dox fluorescence in liposome is self-quenched, which retrieves on releasing Dox from liposomes and dilution in media (Wiles et al, 1997). An immediate burst release occurred in 100 Tat-liposomes, which was not detected in the case of naïve liposomes.…”
Section: In Vitro Releasementioning
confidence: 98%
“…Leakage stability of the liposomes was monitored in RPMI 1640 media containing 30% fetal calf serum (FCS) based on self-quenching of liposomal Dox and dequenching upon Dox release (Wiles et al, 1997). The FCS used in this experiment was not decomplemented by heating at 60 o C. Liposomes were added to the media (1; 9 v/v) and incubated at 37 o C, from which samples …”
Section: In Vitro Releasementioning
confidence: 99%